Autophagy, anoikis, ferroptosis, necroptosis, and endoplasmic reticulum stress: Potential applications in melanoma therapy. Issue 11 (29th April 2019) - Ashrafizadeh, Milad; Mohammadinejad, Reza; Tavakol, Shima; Ahmadi, Zahra; Roomiani, Sahar; Katebi, Majid
Abstract: Melanoma as the most major skin malignancy has attracted much attention, so far. Although a successful therapeutic strategy requires an accurate understanding of the precise mechanisms for the initiation and progression of the melanoma. Several types of cell death mechanisms have recently been identified along with conventional cell death mechanisms such as apoptosis and necrosis. Among those mechanisms, necroptosis, anoikis, ferroptosis, and autophagy may be considered to have remarkable modulatory impacts on melanoma. In the present review, we explain the mechanisms of cell death signaling pathways related to autophagy, ferroptosis, anoikis, necroptosis, and reticulum endoplasmic stress in cells and describe how those mechanisms transduce signals in melanoma cells. Meanwhile, we describe how we can modulate those mechanisms to eliminate melanoma. Abstract : The induction of apoptosis, ER stress, anoikis, necroptosis, and autophagy using special drugs lead to melanoma inhibition. Noteworthy, the inhibition and enhancement of autophagy have the two‐fold role in melanoma elimination.